Luther and the Eucharistic Controversy. Issue 2 (June 2017) - Burnett, Amy Nelson
Abstract: Luther wrote  That These Words of Christ … Still Stand Firm  to teach people what they should believe about the Lord's Supper and to refute the arguments of his opponents. Luther saw the devil as responsible for the rejection of Christ's substantial presence in the bread and wine of the Lord's Supper. The disagreement concerning the eucharist rested on the opposing exegesis of key Scripture texts and had implications for Christology and the understanding of the relationship between theology, science, and human reason. Luther believed that his opponents taught a heretical position that endangered people's souls, and so their ideas could not be tolerated.